PENANGANAN JENAZAH KORBAN BENCANA ALAM BADAN PENANGGULANGAN BENCANA DAERAH DALAM PERSPEKTIF HUKUM ISLAM - fajar rahmat aziz (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2020)
It is the Regional Disaster Management Agency’s (BPBD) onus of South Sulawesi to assist the Governor in organizing regional government administration within the scope of regional disaster management. Among BPBD’s duties in South Sulawesi in handling corpses of natural disaster are: intact Muslim corpses are handled normally, in which the bodies were washed, shrouded, sanctified and buried by following the procedures that have been determined by the Shari'ah. Afterwards, decaying and unrecognizable Muslim corpses were directly shrouded, sanctified then buried. Whilst the large numbers corpses that mixed between Muslims and non-Muslims, were immediately buried and sanctified by religious leaders from each of the existing religious representatives. Hereinafter, the constraints faced by the BPBD of South Sulawesi in handling the corpses of natural disasters include: limited equipment, difficulty in reaching the location and the identification process which requires a long time. The Islamic law view regarding the handling of the natural disasters corpses is that basically, in normal conditions, the corpses must be washed, shrouded, sanctified and buried according to the procedures that have been determined by Islamic law. When a disaster occurs, the handling of the body is still carried out in accordance with the provisions of the Shari'ah but in an emergency situation.